Best Paper Selection (Yearbook of Medical Informatics, 2017)
Chen J, Podchiyska T, Altman R. OrderRex: clinical order decision support and outcome predictions by data-mining electronic medical records. J Am Med Inform Assoc 2016;23:339-48 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5009921/Miotto R, Li L, Kidd BA, Dudley JT. Deep Patient: An Unsupervised Representation to Predict the Future of Patients from the Electronic Health Records. Sci Rep 2016;6:26094 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4869115/Prasser F, Kohlmayer F, Kuhn KA. The Importance of Context: Risk-based De-identification of Biomedical Data. Methods Inf Med 2016;55:347-55 https://methods.schattauer.de/en/contents/archivestandard/issue/2382/manuscript/25994.htSaez C, Zurriaga O, Perez-Panades J, Melchor I, Robles M, Garcia-Gomez JM. Applying probabilistic temporal and multisite data quality control methods to a public health mortality registry in Spain: a systematic approach to quality control of repositories. J Am Med Inform Assoc 2016;23:1085-95 https://academic.oup.com/jamia/article-lookup/doi/10.1093/jamia/ocw010